Bullying, ciberbullying y habilidades sociales en estudiantes. - Ponluiza Cadena, Joselyn Daniela (2024)
The objective of this study focuses on analyzing bullying, cyberbullying, and social skills present in children and adolescent students. The research corresponds to a literature review at a descriptive level. The population consisted of 825 documents published from 2014 to 2024 in Spanish and English, collected through the databases Science Direct, Scielo, Redalyc, ProQuest, Dialnet, and PubMed, among others. The sample was non-probabilistic, based on inclusion and exclusion criteria that allowed obtaining 50 scientific articles based on selection criteria. The bibliographic review was used as a technique; the bibliographic review form and the CRF-QS matrix were used as instruments. The results show that the participation roles involved in bullying and cyberbullying are victim, cyber victim, harasser, cyberbully, aggressor, cyber aggressor, aggressor-victim, cyber aggressor-victim, bystander, and cyber spectator, while the primary social skills involved in bullying and cyberbullying are the search for alternatives, active listening, communication skills, skills related to feelings, empathy, planning, and conflict resolution. Furthermore, information has been collected indicating that the existence of adequate social skills contributes to the decrease in participation in bullying and cyberbullying roles. In conclusion, it is feasible to sustain that most of the students mainly play the role of victim, followed by the observer and aggressor victim, and at a low level, the role of aggressor, regarding the social skills involved in bullying and cyberbullying, aggressors and cyber aggressors present a deficit in empathy and abilities linked to feelings. In contrast, victims present deficiencies in the search for alternatives.